2014
DOI: 10.3389/fpsyg.2014.00346
|View full text |Cite
|
Sign up to set email alerts
|

In (visual) search for a new distraction: the efficiency of a novel attentional deployment versus semantic meaning regulation strategies

Abstract: Cognitive emotion regulation strategies are considered the king’s highway to control affective reactions. Two broad categories of cognitive regulation are attentional deployment and semantic meaning. The basic distinctive feature between these categories is the type of conflict between regulatory and emotional processes for dominance, with an early attentional selection conflict in attentional deployment and a late appraisal selection conflict in semantic meaning. However, prior studies that tested the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 48 publications
3
35
2
Order By: Relevance
“…In one study, HCs were shown images of varying intensities and instructed to either implement engagement reappraisal or disengagement distraction following image exposure. Consistent with theory, the effectiveness of the strategies was comparable following exposure to low intensity images, but distraction was more effective than reappraisal following high intensity image exposure (Sheppes et al, 2014b).…”
Section: Regulationsupporting
confidence: 69%
“…In one study, HCs were shown images of varying intensities and instructed to either implement engagement reappraisal or disengagement distraction following image exposure. Consistent with theory, the effectiveness of the strategies was comparable following exposure to low intensity images, but distraction was more effective than reappraisal following high intensity image exposure (Sheppes et al, 2014b).…”
Section: Regulationsupporting
confidence: 69%
“…This self-regulation strategy has been established to effectively downregulate subjective emotional experiences (Ochsner et al, 2004 ; Ray et al, 2010 ), emotion-expressive behavior (Gross, 1998 ), and amygdala activation (Chen et al, 2017 ). However, recent studies indicate that the controlled reappraisal (CR) initiated by explicit and conscious instructions is less effective and more effortful in high than in low emotional intensity (Sheppes et al, 2014 ; Shafir et al, 2015 ). For example, CR resulted in weaker modulation of self-reported negative experience compared with distraction (Shafir et al, 2015 ) or attentional deployment (Sheppes et al, 2014 ) even though CR was as effective as these strategies in downregulating low-intensity negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in contrast to sad or distressing memories among nontrauma populations, distressing memory recollection in severely traumatized individuals may elicit intense and unwanted negative emotion (e.g., fear); the levels of distress as well as the link to PTS symptom severity in the present data are consistent with this hypothesis. This may be important insofar as emotion regulation via alternative evaluation and meaning making of the negative stimuli may be less adaptive, less effective, and thus less preferred in the context of high negative emotional intensity (Shafir, Schwartz, Blechert, & Sheppes, 2015; Sheppes, Brady, & Samson, 2014; Sheppes, Catran, & Meiran, 2009; Silvers, Weber, Wager, & Ochsner, 2015). Thus, a self-distanced perspective may be functionally incongruent in the context of intense acutely distressing and unwanted autobiographical memories, demanding greater effort and cognitive control than a self-immersed perspective (Silvers et al, 2015).…”
Section: Discussionmentioning
confidence: 99%